A Study On Application Digital Filtering For Audio Signal Processing In Digital Signal Processing - N. M., Nor; Hashim, Nik Mohd Zarifie; S. N., Rosli; Mohamad Zoinol Abidin, Abd Aziz (Innovation And Emerging Technology Group, 2014)
-